Psychometric properties and validity of inventory of symptoms of professional traumatic grief among nursing professionals - Ester Gilart; Anna Bocchino; Isabel Lepiani; Patricia Gilart; Ma José Cantizano Nuñez; María Dueñas (BMC Nursing)
Abstract Background Traumatic grief can exert a considerable influence on the mental and physical well-being of nurses, potentially altering their ability to provide high quality care. This impact is most pronounced in specific contexts such as health emergencies, palliative care and paediatric intensive care units. In the context of the Covid-19 pandemic, health professionals have faced an unprecedented increase in loss and trauma, and this situation is seen as an exacerbating factor in complicated bereavement. Despite the availability of instruments for the assessment of prolonged or pathological grief, there is a pressing need for additional studies that allow for a more accurate understanding and measurement of this phenomenon, filling certain existing methodological gaps. The main purpose of this research is to evaluate the psychometric properties of the Inventory of Symptoms of Professional Traumatic Grief (ISDUTYP), with a view to improving assessment tools in this field. Method Construct validity, reliability, criterion validity, convergent validity and discriminant validity were assessed. The scale’s psychometric properties were tested with 930 nursing professionals. The data were collected between September 2022 and January 2023. Results A total of 930 people took part in the study. The factorial analysis of ISDUTYP showed that, according to eigenvalues and the scree plot, the optimal number of factors was 2. These factors consisted of 13 and 12 items, respectively, and had clinical significance. Factor 1 could be termed “Behavioural Symptoms,” while Factor 2 could be termed “Emotional Symptoms.” Cronbach’s alpha values demonstrated excellent reliability for all scores. In particular, Cronbach’s alpha was 0.964 for the overall score, 0.950 for the behavioural symptoms subscale, and 0.950 for the emotional symptoms subscale. Regarding criterion validity, all expected correlations were statistically significant. Finally, almost all hypotheses defined of convergent and discriminant validity were fulfilled. Conclusions The high reliability and validity of the scale supports its use in research and clinical practice to assess the impact of professional traumatic grief and enhance its treatment. The validated scale for measuring nurses’ grief has significant implications in clinical practice, allowing for the identification and management of nurses’ grief, fostering a healthy work environment, and improving patient care quality.